1984
DOI: 10.1007/bf00222492
|View full text |Cite
|
Sign up to set email alerts
|

The receptor function of galactosyltransferase during cellular interactions

Abstract: The molecular mechanisms that underly cellular interactions during development are still poorly understood. There is reason to believe that complex glycoconjugates participate in cellular interactions by binding to specific cell surface receptors. One class of carbohydrate binding proteins that could serve as receptors during cellular interactions are the glycosyltransferases. Glycosyltransferases have been detected on a variety of cell surfaces, and evidence suggests that they may participate during cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…This possibility is based on the fact that several glycosidases participate in cellular interaction phenomena such as influenza virus (Cronwell and Lonberg-Holm, 1986). Mycoplasma (Roberts et al, 1989) and Trypanosoma cruzi (Schenkman et al, 1991) adhesion/invasion, without necessarily cleaving their substrates (Roseman, 1970;Shur, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is based on the fact that several glycosidases participate in cellular interaction phenomena such as influenza virus (Cronwell and Lonberg-Holm, 1986). Mycoplasma (Roberts et al, 1989) and Trypanosoma cruzi (Schenkman et al, 1991) adhesion/invasion, without necessarily cleaving their substrates (Roseman, 1970;Shur, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…This has been referred to as the Roth hypothesis. Substantial evidence is now available to implicate this mechanism in a variety of cell adhesion or recognition events including cell migration, fertilization, bacterial adhesion, cell differentiation, and immune recognition (Pierce et al, 1980;Shur, 1984). Shur (1982Shur ( , 1983 has recently demonstrated that embryonal carcinoma cells express in their surface membrane a lactosaminoglycan (LAG) composed of repeating Nacetyllactosamine disaccharides.…”
Section: Cell Adhesion Mechanism5mentioning
confidence: 99%
“…The basic molecular mechanism that mediates gamete recognition in mouse is not unique to this one particular window in development, but represents a specific spatially and temporally restricted variation of a more universal developmental program. Collective studies demonstrate that surface GalTase participates in multiple cellular interactions during embryonic development and in the adult [for review, see Shur, 1984;Shur, 19881. Ga1Tase:LAG interactions function during intercellular adhesion in the preimplantation mouse embryo and between F9 embryonal carcinoma cells [Shur, 1983;Bayna et al, 1985, 19881. It has also been suggested that a similar Ga1Tase:LAG cell adhesion system operates between mouse uterine epithelial cells [Dutt et al, 19871. GalTase is the only glycosyltransferase detectable on mesenchymal cell surfaces and a correlation exists between altered surface GalTase activity and genetically altered cell migration [Shur, 19821. In vitro studies of quail neural crest cells and primary embryonic mouse mesenchymal cells have shown that surface GalTase functions during cell migration by binding complementary substrates in the underlying basal lamina [Runyan et al, 1986a;Eckstein et al, 19861.…”
Section: Galtase Functions During Other Cellular Interactions In Devementioning
confidence: 99%